Investigating the relationship between the mechanical properties of plasma polymer-like thin films and their glass transition temperature. Issue 44 (27th October 2021) - Vinx, Nathan; Damman, Pascal; Leclère, Philippe; Bresson, Bruno; Fretigny, Christian; Poleunis, Claude; Delcorte, Arnaud; Cossement, Damien; Snyders, Rony; Thiry, Damien
Abstract : The mechanical properties of plasma polymer-like thin films are investigated and correlated to their glass transition temperature to further develop nanostructured materials. Abstract : This work aims at understanding the influence of the substrate temperature ( T s ) on the viscoelastic properties of propanethiol plasma polymer films (PPFs). By means of state-of-the-art AFM characterization-based techniques including peak force quantitative nanomechanical mapping (PFQNM), nano dynamic mechanical analysis (nDMA) and "scratch" experiments, it has been demonstrated that the mechanical behaviour of PPFs is dramatically affected by the thermal conditions of the substrate. Indeed, the material behaves from a high viscous liquid ( i.e. viscosity ∼ 10 6 Pa s) to a viscoelastic solid (loss modulus ∼ 1.17 GPa, storage modulus ∼ 1.61 GPa) and finally to an elastic solid (loss modulus ∼ 1.95 GPa, storage modulus ∼ 8.51 GPa) when increasing T s from 10 to 45 °C. This behaviour is ascribed to an increase in the surface glass transition temperature of the polymeric network. The latter has been correlated with the chemical composition through the presence of unbound molecules acting as plasticizers and the cross-linking density of the layers. In a second step, this knowledge is exploited for the fabrication of a nanopattern by generating surface instabilities in the propanethiol PPF/Al bilayer system.